Nutritional Composition and Marketable Shelf-Life of Blood Ark Clams and Ponderous Ark Clams - Leslie N. Sturmer; Kimberly L. Morgan; Robert L. Degner (EDIS)
The rapid growth of Florida's hard clam industry over the past decade has motivated aquaculturists to explore alternative molluscan species, which could reduce exposure to production risks and simultaneously promote market expansion. Species diversification could possibly provide some degree of protection against potential disastrous losses associated with a monoculture-based industry. Further, production of other molluscan species could potentially increase sales and profitability, expanding clam consumers' options. The Blood Ark (Anadara ovalis) and the Ponderous Ark (Noetia ponderosa) clams represent two possible production opportunities. This is EDIS document FE568, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2005.